Phytotoxic activity of oil palm frond mulch in combination with selected preemergence herbicide - Dilipkumar Masilamany,; Muhammad Amirul Nordin,; Norhafizah Md Zain,; Ismail Sahid,; Chuah, Tse Seng (Penerbit Universiti Kebangsaan Malaysia, 2020)
The combination of mulch and herbicide is a promising method for weed control which could reduce the frequency of hand weeding. This study was conducted to evaluate the phytotoxic effects of Elaeis guneensis var. tenera (oil palm) frond (OPF) mulch in combination with several pre emergence herbicides on the inhibition of goosegrass (Eleusine indica (L.) Gaertn), slender cyperus (Cyperus distans L.f.) and coat buttons (Tridax procumbens (L.)) under greenhouse conditions. Three rates of dinoterb, oxyfluorfen, and isoxaflutole were respectively, applied with or without OPF mulch at 3.5 t ha−1. The results showed that the weed inhibition provided by the dinoterb-treated OPF mulch (60 to 100%) was greater than dinoterb (0 to 50%) or OPF mulch (0 to 60%) applied alone across all the application rates and bioassay species. The oxyfluorfen-treated OPF mulch also gave greater inhibition (70 to 90%) of T. procumbens than those provided by oxyfluorfen (20 to 40%) or the OPF mulch alone (55 to 60%). However, an increase in inhibition of C. distans and E. indica was only evident at a low rate of oxyfluorfen when combined the OPF mulch. Weed inhibition was noted with increasing rates of isoxaflutole alone but the isoxaflutole-treated OPF mulch did not lead to further inhibition of weeds except for T. procumbens. These results suggest that the phytotoxicity of OPF mulch in combination with herbicides are dependent on weed species, herbicides, and application rates, with dinoterb being the most compatible with OPF mulch when combined